2009
DOI: 10.1111/j.1439-0469.1997.tb00412.x
|View full text |Cite
|
Sign up to set email alerts
|

Karyotypes of the most primitive catfishes (Teleostei: Siluriformas: Diplomystidae)

Abstract: Karyotypes of Diplomystes camposensis and Dipfomystes nahuelbutaensis were the same diploid number (n = 56). The chromosome formula for D. camposensis was 16 metacentric + 24 submetacentric + 8 subtelocentric + 8 telocentric chromosomes and for D. nahuelbutaensis was 14 metacentric + 26 submetacentric + 8 subtelocentric .t 8 telocentric chromosomes. In contrast, the differences in the chromosomal C-banding patterns between these species was large. For instance, chromosome pairs 5, 6, and 7 of D. nahuelbutaensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The variation in chromosome morphology including size and type of chromosome might be due to the excessive chromosomal contraction as a consequence of higher dose or over-exposure to colchicine, improper fixation of tissue, methods of chromosomal preparation and classification (Zhang and Reddy 1991). However, these variations, especially the variation in 2n, may also arise from chromosomal aberrations or rearrangements followed by population isolation during evolutionary process (Chu andBender 1961, Campos andCuevas 1997) as the karyotype evolution found in C. gachua and C. striata (Supiwong et al 2009. The more cytogeographic investigation is needed in these species to reveal and confirm intra-and inter-specific karyotype variations.…”
Section: Resultsmentioning
confidence: 99%
“…The variation in chromosome morphology including size and type of chromosome might be due to the excessive chromosomal contraction as a consequence of higher dose or over-exposure to colchicine, improper fixation of tissue, methods of chromosomal preparation and classification (Zhang and Reddy 1991). However, these variations, especially the variation in 2n, may also arise from chromosomal aberrations or rearrangements followed by population isolation during evolutionary process (Chu andBender 1961, Campos andCuevas 1997) as the karyotype evolution found in C. gachua and C. striata (Supiwong et al 2009. The more cytogeographic investigation is needed in these species to reveal and confirm intra-and inter-specific karyotype variations.…”
Section: Resultsmentioning
confidence: 99%
“…Knowledge of karyotype characteristics allows a better understanding of a species' phylogenetic status. In general, with in specific taxonomic categories, primitive groups have more telocentric chromosomes, while specialized groups have more metacentric or submetacentric chromosomes [25]. More primitivefish species have a higher number of telocentric and subtelocentric chromosomes, fewer or nometacentric and submetacentric chromosomes, and a lower total number of chromosome arms [26].…”
Section: Discussionmentioning
confidence: 99%
“…The distinctness of D. nahuelbutaensis and D. camposensis is supported by numerous morphological characters (see diagnoses above) and information provided by their karyotypes (including specimens of D. camposensis from Toltén and Valdivia Basins). Although the diploid number of chromosomes and chromosomes formulae are comparable, differences in C-banding are present ( Campos, Arratia & Cuevas, 1997 ). According to Muñoz-Ramírez et al (2014) the populations found in the Bío-Bío Basin would represent a new species, but not D .…”
Section: Final Commentsmentioning
confidence: 99%
“…The population of Bío-Bío Basin that appears in their results as genetically distinct would be a new species, not D. nahuelbutaensis . Curiously, the authors assumed that the identification of specimens can be determined by their geographic distribution and failed to mention that the diagnoses of the three nominal species, D. chilensis , D. nahuelbutaensis , and D. camposensis are supported by numerous morphological characters ( Arratia, 1987 : 13, 34, 45) and also by genetic characteristics of D. nahuelbutaensis and D. camposensis based on specimens from the upper part of Bío-Bío and Imperial Basins, and Toltén and Valdivia Basins, respectively ( Campos, Arratia & Cuevas, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation